Peptídeos antimicrobianos sintéticos: atividade antifúngica e mecanismos de ação - Lima, Patrícia Gomes (2021)
Antimicrobial peptides (AMPs) are components of the innate immune system, present in all living beings, capable of participating in the defense against infections by fungi, bacteria, parasites and viruses. Among the characteristics of AMPs, their mechanism of action stands out, since it usually involves the destabilization of the cell membrane, representing a low possibility of resistance development by microorganisms. This characteristic meets the need to develop alternative ways to combat infections by resistant microorganisms. However, naturally occurring PAMs may have some undesirable characteristics for their therapeutic application, such as instability and toxicity. Thus, Mo-CBP3 proteins, isolated from the Moringa oleifera seed, and Rc-2S-Alb, protein from the Ricinus communis seed cake, which have antimicrobial properties, were used as a model for the design of synthetic peptides. Such peptides, Mo-CBP3-PepI, Mo-CBP3-PepII, Mo-CBP3-PepIII, RcAlb-PepI, RcAlb-PepII and RcAlb-PepIII, were evaluated for their in vitro antimicrobial activity against important fungi in the health field, such as Candida spp., Trichophyton rubrum and T. mentagrophytes. Mo-CBP3-PepI and Mo-CBP3-PepII showed high antifungal activity against C. albicans. Regarding the dermatophyte fungi, Mo-CBP3-PepI, Mo-CBP3-PepII, Mo-CBP3-PepIII inhibited the germination of microconidia and the mycelial growth of T. mentagrophytes, while RcAlb-PepI, RcAlb-PepII and RcAlb-PepIII inhibited germination of microconidia and mycelial growth of T. rubrum. Scanning electron microscopy and atomic force analyzes showed that treatment with the peptides caused morphological damage to fungal cells, such as cell wall deformation and leakage of cytoplasmic content. Additionally, the modes of action of the AMPs were analyzed through fluorescence microscopy, being detected the overexpression of reactive oxygen species and the formation of pores in the cell membrane of these fungi. In addition, the tested AMPs weren’t toxic and demonstrated a synergistic relationship with the commercial antifungals nystatin and griseofulvin. Thus, such peptides have high potential as alternative molecules for the development of new drugs for the treatment of fungal infections, both alone and as adjuvants to existing drugs.